Asthma control and acute healthcare visits among young adults with asthma—A population‐based study. (18th September 2019) - Selberg, Stina; Hedman, Linnea; Jansson, Sven‐Arne; Backman, Helena; Stridsman, Caroline
Abstract: Aims: To study asthma control and acute healthcare visits among young adults with asthma. Background: Despite the access to effective treatment and nursing interventions, poor asthma control is still common among individuals with asthma. However, studies describing clinical characteristics among young adults with asthma are rare. Design: A population‐based cohort study. Methods: In 2015, as a part of the OLIN paediatric cohort I (recruited in 1996 at age 7–8 years), N  = 2, 291 young adults (27–28 years) completed a postal questionnaire survey including questions on asthma and respiratory symptoms. Of these, N  = 280 (12%) were identified as having current asthma and were further studied. Results: Of those with current asthma, women reported respiratory symptoms and smoking to a greater extent than men. Approximately one‐fourth had uncontrolled asthma and acute healthcare visits due to asthma was reported by 15% of women and 8% of men. Uncontrolled asthma was associated with smoking, lower educational level, use of reliever treatment most days, and acute healthcare visits. Acute healthcare visits due to asthma were associated with periodic use of regular controller treatment also after adjustment for uncontrolled asthma. Conclusion: The result indicate poor adherence to asthma treatment which may lead to decreased asthma control and acute healthcare visits. Impact: Most young adults with asthma are diagnosed and treated in primary care, ideally in a team with a nurse. The main findings highlight the need for evidenced‐based nursing interventions, contributing to a more efficient asthma management in primary care. Abstract : 目的: 研究哮喘青年患者的哮喘控制和急性保健访问。 背景: 尽管可以获得有效的治疗和护理干预, 但哮喘控制不良在哮喘患者中仍然很常见。然而, 描述哮喘青年患者临床特征的研究很少。 设计: 基于人群的队列研究。 方法: 2015年, 作为OLIN儿科队列一(1996年招募, 年龄为7‐8岁)的一部分, N = 2291名年轻人(27‐28岁)完成了一项邮寄问卷调查, 其中包括关于哮喘和呼吸道症状的问题。其中, N = 280(12%)被确定为患有哮喘并进行了进一步的研究。 结果: 在目前患有哮喘的患者中, 女性报告的呼吸道症状和吸烟情况比男性更多。大约有1/4的人患有不能控制的哮喘, 15%的女性和8%的男性报告了因哮喘而进行的急性保健访问。哮喘失控与吸烟、较低的教育水平、大多数日子使用救济治疗和急性保健访问有关。由哮喘引起的急性保健访问与定期使用常规控制者治疗相关, 在对不能控制的哮喘进行调整后也是如此。 结论: 结果表明, 没有坚持对哮喘进行治疗可能导致哮喘控制和急性保健访问下降。 影响: 大多数患有哮喘的年轻人在初级保健中得到诊断和治疗(最好是在有护士的团队中)。主要的调查结果强调了基于证据的护理干预的必要性, 有助于在初级护理中更有效地管理哮喘。